A new genus and species of pilumnid crab (Decapoda: Brachyura: Pilumnidae) symbiotic with the sponge Callyspongia Duchassaing & Michelotti, 1864 (Porifera: Demospongiae: Callyspongiidae) from Lombok, Indonesia; the identity of Pseudactumnus pestae; and a review of symbiosis in the Pilumnidae. Issue 6 (14th August 2020) - Ng, Peter K L; Rahayu, Dwi Listyo
Abstract: A new genus and new species of pilumnid crab, Ericiolumnus symbioticus (Decapoda: Brachyura), is described from the sponge Callyspongia Duchassaing & Michelotti, 1864 (Porifera: Callyspongiidae) in reefs in Lombok, Indonesia. The new taxon is characterized, among several characters, by the unusual shape of the carapace, which possesses sharp anterolateral teeth armed with secondary spinules, and prominently spinulous ambulatory legs. Another pilumnid, Pseudactumnus pestae Balss, 1933, is shown to be a junior synonym of Actumnus asper (Rüppell, 1830 ). The pilumnid genus Pseudactumnus Balss, 1933 is additionally synonymised with Actumnus Dana, 1851 . A review of symbiosis in Pilumnidae is also presented.